Congenital complete absence of GH, TSH and PRL in infants: a consequence of Pit-1 gene deletion. - C. Preeyasombat (2018)
The patient was the first child of a short mother (140 cm) born at term with a birthweight of 2,700 g. On arrival, she was 1 4/12-year-old, weighed 4,150 g and 47 cm long. Her bone age was at the 6 month-old level. Endocrine investigation revealed undetectable plasma growth hormone (GH), thyrotropin (TSH) and prolactin (PRL) levels. CT scan of ovaries revealed bilateral ovarian agenesis in spite of normal, 46 XX karyotype. MRI of the brain did not demonstrate intracranial tumor or congenital malformation. Peak plasma GH level after oral clonidine provocation, insulin induced hypoglycemia, and I.V. GH-RF stimulation were 0.6, 0, and 0 ng/ml respectively. Peak plasma TSH response after I.V. TRH stimulation was 0.04 microU/ml. The patient could not secrete PRL at any time after insulin induced hypoglycemia, TRH and metoclopramide stimulations. On the other hand the child had elevated basal plasma cortisol (38 micrograms/dl at 8.00 AM) and raised 24 hr urinary 17 OHCS excretion (50 mg/1 g Cr against normal value of 3 mg/1 g Cr) without evidence of Cushing syndrome probably indicate partial glucocorticoid resistance. Peak plasma cortisol responses after intravenous metoclopramide and insulin induced hypoglycemia were 46 and 42.9 micrograms/dl respectively. Dexamethasone administration reduced plasma cortisol to 2.9 micrograms/dl. The child had also elevated basal plasma FSH (36 microU/ml) and LH (5 microU/ml) with further elevation to the peak of 123 and 99 microU/ml respectively after LHRH stimulation. All evidence suggested the diagnosis of congenital complete absence of GH, TSH, and PRL which is characteristic of Pit-1-gene deletion.(ABSTRACT TRUNCATED AT 250 WORDS)